Investigation of the STOX1 polymorphism on lumbar disc herniation. Issue 1 (13th November 2019) - Yang, Xuejun; Li, Feng; Xin, Daqi; Huang, Zhi; Xue, Jianmin; Wang, Bo; Da, Yifeng; Xing, Wenhua; Zhu, Yong
Abstract: Background: Lumbar disc herniation (LDH) is a common musculoskeletal disorder affliction and associated with several genes polymorphism. Storkhead box 1 ( STOX1 ) gene is a transcriptional factor related with several signaling pathways including inflammatory pathway. However, little is known about single‐nucleotide polymorphisms (SNPs) of STOX1 associated with LDH risk. Methods: We conducted a case–control study among 508 LDH cases and well‐matched 508 controls, and six candidate SNPs in STOX1 were genotyped by Agena MassARRAY. Chi‐squared test, genetic model, and haploview analysis were used to evaluate associations. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated by unconditional logistic regression. Results: In the allelic model analysis, we found the minor allele "T" of rs7903209 and "A" of rs4472827 were associated with an increased risk of LDH ( p = .029, p = .016). Furthermore, in the genotype model analysis, rs7903209 polymorphism was associated with the increased susceptibility of LDH based on dominant ( p = .033) and additive model ( p = .024); and rs4472827 variant was found to play a harmful role in the LDH risk based on genotype ( p = .014), dominant ( p = .012), and additive model ( p = .015). In the haplotype analysis, the haplotype "GT" in block (rs10998461 and rs10998468) decreased LDH risk (OR = 0.7, 95% CI = 0.52–0.93, p = .016). Functional assessment indicated that rs7903209 and rs4472827 polymorphisms may influence the expression of STOX1 . Conclusion: Our results provide evidence for polymorphisms of rs7903209 and rs4472827 in STOX1 associated with LDH risk in Chinese Han population. Abstract : We aimed to explore the association between STOX1 polymorphisms and LDH risk, and we found that STOX1 might be a functional factor for the occurrence and development of LDH.